Technology Creation-Need of the Nation - Gupchup, Vijay N. (Journal of Engineering Education Transformations, 2006)
For centuries gone by, man has been engaged in making every effort to face his environment with a view to surmounting adversities and exploiting advantages which nature has provided. To live peacefully, his needs were concentrated towards getting food and water, protecting his self against natural hardships through appropriate clothing and shelter.